The stolen queen : a novel - Davis, Fiona, 1966- (Dutton, 2025)
"Egypt, 1936: When anthropology student Charlotte Cross is offered a coveted spot on an archaeological dig in Egypt's Valley of the Kings, she leaps at the opportunity. But after an unbearable tragedy strikes, Charlotte knows her future will never be the same. New York City, 1978: Eighteen-year-old Annie Jenkins is thrilled when she lands an opportunity to work for iconic former Vogue fashion editor Diana Vreeland, who's in the midst of organizing the famous Met Gala, hosted at the museum and known across the city as the "party of the year." Though Annie soon realizes she'll have her work cut out for her, scrambling to meet Diana's capricious demands and exacting standards. Meanwhile, Charlotte, now leading a quiet life as the associate curator of the Met's celebrated Department of Egyptian Art, wants little to do with the upcoming gala. She's consumed with her research on Hathorkare-a rare female pharaoh dismissed by most other Egyptologists as unimportant. That is, until the night of the gala. When one of the Egyptian art collection's most valuable artifacts goes missing . . . and there are signs Hathorkare's legendary curse might be reawakening. As Annie and Charlotte team up to search for the missing antiquity, a desperate hunch leads the unlikely duo to one place Charlotte swore she'd never return: Egypt. But if they're to have any hope of finding the artifact, Charlotte will need to confront the demons of her past-which may mean leading them both directly into danger"--